(des formes de vie) : une écologie des pratiques artistiques. - Leibovici, Franck (Aubervilliers ; Paris : Les Laboratoires d'Aubervilliers : Éditions Questions théoriques, 2012)
agence ; BADco. ; Baladrán, Zbyněk ; Becker, Howard S. ; Faulkner, Robert R. ; Bérard, Stéphane ; Boone, Nicolas ; Boucand, Gaëlle ; Naccache, Marion ; Chaton, Anne-James ; Chong, Heman ; Cirauqui, Manuel ; Clainchard, Matthieu ; Collectif 1.0.3 ; Cometti, Jean-Pierre ; Contour, Catherine ; Copeland, Mathieu ; Cruzvillegas, Abraham ; Cvejić ; Damasceno, José ; Danos, Frédéric ; Deck, François ; Dehn, Jochen ; Delos Reyes, Jen ; Denimal, Laurence ; Dockx, Nico ; Edvardsen, Mette ; Etchells, Tim ; Fishkin, Vadim ; Gander, Ryan ; Genod, Yves-Noël ; Hagaman, Dianne ; Heidsieck, Bernard ; Hervé, Louise ; Maillet, Chloé ; Hills, Henry ; Högström, Martin ; Hybris konstproduktion ; Irwin ; Jarmusch, Tom ; Joseph, Manuel ; Kläring, Julia ; ; Kurant, Agnieszka ; Kurdian, Gérald ; László, Gergely ; Lester, Gabriel ; Linke, Armin ; Hanappe, Peter ; Mayer, Christian ; Mettler, Yves ; Miller, Paul D. (dj spooky) ; Mohaiemen, Naeem ; Neto, Ernesto ; Parendeau, Émilie ; Petitgand, Dominique ; Pietroiusti, Cesare ; Plan b ; Potrč, Marjetica ; Quenum, Chloé ; Reyes, Pedro ; Rimbaud, Robin (scanner) ; Roeskens, Till ; Sadr Haghighian, Natascha ; Santkin, Manon ; Santoro, Vittorio ; Schweizer, Maya ; Siepen, Nicolas ; Singer, Leah ; Takala, Pilvi ; Thurnauer, Agnès ; Todosijevič, Raša ; Tomaselli, Alice ; Vanhee, Sarah ; Vatamanu, Mona ; Tudor, Florin ; Viannay, Clotilde ; Vidokle, Anton ; Vinitsky, Yonatan ; Weiner, Lawrence
boek